Regional dominance and its role in selecting sites Religious conflict in the East - السهلاني عبد العزيز عبد الهادي جواد عزيز (Al-Adab Journal, 2019)
This research stems from the observations that point to the role of the regional powers in guiding the escalation of the conflict in the East and the Arab region, which lies in the problem of regional hegemony and religious conflict, which necessitates research as it is of great importance to the eastern region. In particular, intellectually and ethnically through the conflict. The research consists of four topics, the first of which focuses on the problem of hegemony and religious conflict and the desire of states to drain the natural and human resources of the East. The importance of research is to show and clarify the hidden sides behind these The aim of the study is to find solutions and non-recurrence of conflicts, especially in areas where the causes were eliminated. The second topic dealt with regional hegemony as a concept and forms of hegemony, study of the political region, differentiation between the concepts of conflict and conflict and clarification of the concept and models of religious conflict. The Arab region and the study of the Syrian Republic in terms of location, reasons and parties that contributed to the emergence of religious conflict and study the Republic of Iraq because it was subjected to that challenge in terms of location and reasons and parties involved in the Of the conflict that took place in some areas. The fourth topic focused on the Russian and American role in the conflict areas .